(untitled) (Journal of actual problems of jurisprudence, 2018)
This article discusses the form of protective speech lawyer. The author dwells on the requirement of protective speech lawyer during the judicial reasons. The author arrives at the conclusion that carefully designed protective it is of great educational value. The article emphasizes that the evidentiary and persuasive speech protection, based on the lawyer has done a lot of preparatory work. Key words: advocate, advocacy, judicial debates, performance of advocate in defence, oratorical art, representative on errand.